IML204: Information and Communication Technology in Libraries / College of Computing, Informatics and Mathematics - UiTM, College of Computing, Informatics and Mathematics (2023)
This course provides a general overview of information technology and its essential principles. Both the basic principles of managing information and communication technology (ICT), information systems and their application to libraries will be examined. Key topics will include the basic technical infrastructure and the impact of emerging technologies on information systems in libraries.